Mitochondrial DNA polymorphisms in individuals died from sudden cardiac death - M. V. Golubenko; A. V. Tsepokina; R. R. Salakhov; V. N. Maksimov; A. A. Gurazheva; B. A. Tkhorenko; A. V. Ponasenko (Фундаментальная и клиническая медицина)
Aim. To identify associations of mtDNA polymorphisms with sudden cardiac death.Materials and Methods. DNA was isolated from the cardiac tissue excised during the autopsy from individuals who died from sudden cardiac death (n = 260). The frequencies of the most common European mtDNA haplogroups (H, U, T and J) were determined using restriction fragment length polymorphism analysis. In addition, we performed a comparative analysis using previously published data on mtDNA polymorphisms in the West Siberian population.Results. The distribution of mtDNA haplogroups in the patients who died from sudden cardiac death was similar as in the general population: 40% for haplogroup H, 23% for haplogroup U, 12% for haplogroup T and 6.5% for haplogroup J. We found no significant differences regarding the frequency of mtDNA haplogroups in individuals who died from sudden cardiac death and the population level.Conclusion. We discovered no associations of H, U, T, and J mtDNA haplogroups with sudden cardiac death. These results indicate the necessity of a detailed analysis of mitochondrial genome to determine mtDNA variants associated with sudden cardiac death.